PRODUKSI GAS HIDROGEN DARI LIMBAH KALENG MINUMAN DENGAN PEMANFAATAN SISTEM FOTOVOLTAIK - Erlinawati, Erlinawati (KINETIKA, 2018)
Hydrogen is a more friendly alternative fuel because its only produces moisture.The electrolysis method in alkaline solutions is the simplest way to produce hydrogen. In addition, the use of aluminum cans can increase the amount of gas production. This process use photofoltaic as a direct current supply for electrolysis. This study uses concentration of KOH is 1, 1.5 and M with a mass variation of aluminum 10 gr, 30 gr, and 50 gr. In the process, utilization of circulation and electrolyte regeneration is carried out. Based on the results of the study showed that by utilizing the regeneration process can increase the production of hydrogen gas. And it was found that the more mass of aluminum used with the same concentration can produce more hydrogen gas. The largest volume of hydrogen gas is obtained in aluminum waste with a concentration of 1 M KOH and Al 50 gram which is equal to 12.359 ml/ s. Then also obtained research results from the utilization of fotovoltaic obtained hydrogen gas volume 11.7326 ml/ s current of 13.51A with a concentration of 2M